Child-Protection Systems – Serbian Perspective - Vlašković, Veljko (Child-Protection Systems, 2025)
Abstract:It is in the best interests of the child that he or she grows up with both parents who take care of him or her jointly within a functional family. However, certain situations necessitate support and assistance for the child and the family from society and the state for the child to continue to exercise his or her rights within the primary family environment. If such support and assistance is sufficient, the child may be temporarily or permanently deprived of a family environment, states are obliged to provide the child with alternative care. Through the structure of a country-report, this paper presents the main features of the child protection system in Serbia and the way in which Serbia respects the obligation to provide the child at risk with the right to special protection and assistance in accordance with Art. 20 of the UN Convention on the Rights of the Child and the UN Guidelines for the Alternative Care of Children. Although the outlook provided is general, it is an integral overview of the child protection system in Serbia, including the normative framework of protection, guiding principles that are applied when providing support and protection, the structure of the child protection system, followed by a review and consideration of a wide range of welfare services and protective measures that are available to children and families in crisis situations. Special attention is paid to the child’s participation within the protection system, as well as the position of children with disabilities and children in street situations, who are extremely vulnerable groups. Keywords: child rights, child protection system, Serbia, support, social services, measures of protection, alternative care